Curricular Revision in Rural Special Education: A Multicultural Approach - Peggy L. Anderson; Henry B. Reiff; Audrey D. McCray (Educational Considerations, 1989)
In order to meet the needs of rural exceptional students who come from ethnically and/or linguistically diverse backgrounds, university training programs must move beyond monocultural approaches.